1994
DOI: 10.3109/10520299409106312
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Proliferating Cell Nuclear Antigen in Tissues of Three Small Fish Species

Abstract: An immunohistochemical assay for proliferating cell nuclear antigen (PCNA) identifies cells in all active phases of the cell cycle. In this study, PCNA methodology, which was developed primarily for mammalian tissues, was adapted to three small fish species, medaka (Oryzias latipes), guppy (Poecilia reticulata), and western mosquitofish (Gambusia affinis) that are used in carcinogenesis bioassays and environmental sentinel studies. Our study showed that PCNA can be identified in routinely processed, paraffin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 20 publications
1
58
0
Order By: Relevance
“…Clone PC10 has been successfully used in many studies of cell proliferation in mammals (Hall et al, 1990;Preziosi et al, 1995;Start et al, 1992). It has also been reported that clone PC10 gives the best results in PCNA detection in fish tissues (Ortego et al, 1994). The only study on immunological PCNA detection in insect tissue sections to our knowledge also used clone PC10 as the primary antibody (Yamaguchi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Clone PC10 has been successfully used in many studies of cell proliferation in mammals (Hall et al, 1990;Preziosi et al, 1995;Start et al, 1992). It has also been reported that clone PC10 gives the best results in PCNA detection in fish tissues (Ortego et al, 1994). The only study on immunological PCNA detection in insect tissue sections to our knowledge also used clone PC10 as the primary antibody (Yamaguchi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining was carried out using the Unitect Avidin-Biotin-Peroxidase Immunohistochemistry Detection System Kit (Oncogene Science, Cambridge, MA, USA), which contains the recombinant PCNA mouse monoclonal PC10 antibody shown to interact with fish PCNA antigen (Ortego et al 1994). The procedure was a modification of that suggested by the supplier.…”
Section: Pcna Immunohistochemistrymentioning
confidence: 99%
“…Endogenous peroxidase was quenched by treating sections in darkness for 10 min with 3% (v/v) hydrogen peroxide. Following a rinse in distilled water, the sections were subjected to an antigen-retrieval procedure (Ortego et al 1994), which involved heating in a microwave oven (450 W) in 1% (v/v) anhydrous zinc sulphate for 3 min, resting for 1 min and heating a further 3 min. After cooling for 15 min, sections were rinsed in distilled water and placed in 0.5% (v/v) Tween 20 in PBS (137 mM NaCl, 29 mM NaH 2 PO 4 ·H 2 O and 9 mM Na 2 HPO 4 , pH 7.4; referred to here as PBS-A) for 5 min.…”
Section: Pcna Immunohistochemistrymentioning
confidence: 99%
“…containing the recombinant PCNA mouse monoclonal PC10 antibody shown to interact with fish PCNA antigen (Ortego et al 1994). In brief, endogenous peroxidase was quenched by treating sections in darkness for 10 min with 3% hydrogen peroxide.…”
Section: Pcna Immunohistochemistrymentioning
confidence: 99%
“…In brief, endogenous peroxidase was quenched by treating sections in darkness for 10 min with 3% hydrogen peroxide. Following a rinse in distilled water, the sections were subjected to an antigen retrieval procedure (Ortego et al 1994) that involved heating the sections in a microwave oven (450 W) in 1% anhydrous zinc sulphate for 3 min, resting for 1 min, and heating for a further 3 min. After being cooled for 15 min, sections were rinsed in distilled water and placed in 0.5% Tween 20 in phosphate-buffered saline (PBS-A: 137 mM NaCl, 29 mM NaH 2 PO 4 •H 2 O, 9 mM Na 2 HPO 4 , pH 7.4) for 5 min.…”
Section: Pcna Immunohistochemistrymentioning
confidence: 99%